ANALISIS PENDAPATAN BURUH WANITA KELAPA SAWIT (Elaeis guinensis, jacq) DAN KONTRIBUSI TERHADAP PENDAPATAN KELUARGA DI AFDELLING IX PTP. MITRA OGAN KABUPATEN OGAN KOMERING ULU (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2016)
Analysis of Labor Women's Palm (Elaeis guinensis, Jacq) And Contribute To Income Families In Afdelling Ix PTP. Mitra Ogan Regency Ulu purpose of this study was (1) Calculate income women laborers palm in PTP Mitra Ogan Afdelling IX of the disabled, (2) Calculate the contribution to women's labor palm in PTP Mitra Ogan Afdelling IX of the disabled to the family income , This research was conducted in Afdelling IX PT. Mitra Ogan Ulu Regency, where the determination of the area was done intentionally (purposive). This area was chosen as the study sites because this area there are basic elements to be studied, especially in terms of the role of women workers palm. The results showed that (1) - Average income of women workers in oil palm farming Mitra Ogan Afdelling PTP IX is USD 8,157,783.33 per year. (2) The contribution towomen workers in oil palm farming PTP Mitra Ogan per year is 47.01 percent or Rp 8,157,783.33 of the total family income of Rp 18,247,983.33 per year.